Practice recommendations regarding parental presence in NICUs during pandemics caused by respiratory pathogens like COVID-19 - Campbell-Yeo, Marsha; Bacchini, Fabiana; Alcock, Lynsey; Mitra, Souvik; MacNeil, Morgan; Mireault, Amy; Beltempo, Marc; Bishop, Tanya; Campbell, Douglas M.; Chilcott, Addie; Comeau, Jeannette L.; Dol, Justine; et al. (Frontiers in Pediatrics, 2024)
Aim To co-create parental presence practice recommendations across Canadian NICUs during pandemics caused by respiratory pathogens such as COVID-19. Methods Recommendations were developed through evidence, context, Delphi and Values and Preferences methods. For Delphi 1 and 2, participants rated 50 items and 20 items respectively on a scale from 1 (very low importance) to 5 (very high). To determine consensus, evidence and context of benefits and harms were presented and discussed within the Values and Preference framework for the top-ranked items. An agreement of 80% or more was deemed consensus. Results After two Delphi rounds (n = 59 participants), 13 recommendations with the highest rated importance were identified. Consensus recommendations included 6 strong recommendations (parents as essential caregivers, providing skin-to-skin contact, direct or mothers' own expressed milk feeding, attending medical rounds, mental health and psychosocial services access, and inclusion of parent partners in pandemic response planning) and 7 conditional recommendations (providing hands-on care tasks, providing touch, two parents present at the same time, food and drink access, use of communication devices, and in-person access to medical rounds and mental health and psychosocial services). Conclusion These recommendations can guide institutions in developing strategies for parental presence during pandemics caused by respiratory pathogens like COVID-19